Investigation of Oleogel Properties Prepared by Pickering Emulsion-Templated Stabilized with Solid Particles of Basil Seed Gum and Isolated Soy Protein as a Fat Substitute in Cream - Sima Naji-Tabasi (Pizhūhish va Nuāvarī dar ̒Ulūm va Sanāyi̒-i Ghaz̠āyī, 2020)
According to the multiple role of fat in food products, it is necessary to use a substance as a substitute of fat to maintain the rheological, texture and sensory characteristics of low-fat products. In this study, oleogel system was applied to produce low-fat product. Pickering emulsion-templated was applied to produce oleogels. Isolated soy protein (ISP) and basil seed gum (ISP-BSG) were used for the preparation of Pickering. ISP-BSG particles were prepared with different mass ratios of ISP-BSG, 1:0, 1:1, 2:1 and 3:1 and named 1S:0B, 1S:1B, 2S:1B and 3S:1B, respectively. The type and structure of the Pickering used affected the amount of oil retention in the oleogel (p < /em><0.05). The presence of basil seed gum in a suitable ratio with protein (2S:1B) caused a more stable oleogel, higher mechanical strength, and more compact network. Finally, the oleogels were prepared with better oil bonding capacity. The highest and lowest thermal stability rates were for the 2S:1B and 1S:1B samples, respectively. The highest and lowest consistency levels were observed in 2S:1B and 1S: 0B samples, respectively (p < /em><0.05). Investigation of the viscoelastic properties confirmed the gel formation in the oleogel system. According to the stability and textural properties of oleogel samples, two formulas 1S:0B and 2S:1B were used to produce cream with reduced fat (5, 10 and 15%). The highest overall acceptance was obtained in the 2S:1B sample with a 5% reduction in fat, which had no significant difference with control cream.